The organization of the teachers’ unions in the Paraná Municipal Education System: Mapping the relation between union representation and teacher remuneration - Gouveia, Andréa Barbosa (Education Policy Analysis Archives, 2019)
The paper analyses the structure of public teachers’ unions in the 399 cities in the Brazilian state of Paraná and characterizes the conditions of teachers’ remuneration in the years 2008 and 2016, based on Annual Social Information Relation (RAIS) data. It assumes the organization of the unions as a political component, in order to understand the variations in the conditions of teachers’ valorization, by identifying four kinds of organization: own unions, public servants’ unions, affiliation to the state union, and intermunicipal unions. The mapping has contributed to broaden the understanding of teachers’ unionism, both in relation to the systemic structure (Habermas, 1999) of work exploration and the organization of the education systems. Among the evidences regarding remuneration is the growth of the teachers’ average pay in the period that marks a brief cycle of teachers’ valorization policies and the diversity of forms of union organization in the municipalities of Paraná.